Novice teachers experiences on the development of professional identities during practicum - Setlhako, Motladi Angeline (Penerbit Universiti Kebangsaan Malaysia, 2019)
Empirical research confirms that developing a professional identity consists of well-founded theoretical learning and the ability to use practical skills needed in a classroom and a school with ingenuity and flexibility begins during the practicum. This study investigates the experiences of school-based mentor teachers and novice teachers in relation to the development of professional identity of prospective teachers. To meet these objectives a qualitative case study design with a total of ten participants was used. Data were collected from mentors' reports, observations of facilitation of the process and semi-structured interviews with mentors as well as the novice teachers at the end of the same teaching experience. The theoretical framework based on social constructivism as a sociological theory informed the study. The findings showed that mentoring is valuable to mentors and novice teachers. In their roles as mentors the study revealed identities which were assured experts, comfortable in the I-position of experienced professionals. The study concluded that prolonged teaching practice will help in the formative development of aspirant teachers as the extended teaching practice forms part of continuous induction of students into the teaching profession.